90 - AUDIOLOGICAL PROFILE IN CHILDREN AGED FROM SEVEN TO TEN YEARS OLD IN THE VISCONDE DE MAUÁ SCHOOL ASSISTED BY SESI-DR/AMAPÁ HEALTH CENTER IN 2009. (Fiep Bulletin - online, 2011)
The present study promotes a casuistry analysis of the auditive loss evidenced in a group of students in the age group from seven to ten years of age of the Escola Barão of Mauá - SESI-DR-AP, which was accomplished in 2009 starting from a tracking process promoted by the Medical Service of the Clinic of institutional Fonoaudiology. The study had as starting point a sensitization process together with the parents or tutors of the students and in order to take their consent. The data were extracted, consolidated and analyzed, aiming to quantify and to characterize the auditive loss, besides evaluating the correlation between the lesion and the continuous use of headphones. 369 children were observed, it was evidenced a high occurrence of cases (86/369) and the effective association between the use of headphones and the casuistry in 97,7% of the cases. It was identified, therefore, that the problem has significant dimensions and it suggests the need of the implementation of advanced models of tracking to minimize this severe impact over in the population, especially in children.
Keywords: Infant Auditive loss; Amazon; Brazil